Analysis of Scrum Project Management Maturity in Software Development - Komang Dreibayu Anggara; Putu Adiguna Permana; Komang Yuli Santika; Adhi Agam Pradhana (bit-Tech, 2026)
The increasing need for adaptive and responsive software development has encouraged organizations to adopt Scrum as an Agile project management framework. However, the formal use of Scrum does not always indicate that its practices have been implemented consistently or maturely across projects. Software House XYZ has implemented Scrum since 2017, but no formal maturity assessment had previously been conducted. This study aims to analyze the maturity level of Scrum project management in software development projects and identify Key Process Areas that require improvement. A quantitative descriptive approach was employed using the Scrum Maturity Model and Agile Maturity Model. The study assessed three Scrum-based projects, namely Project A, Project B, and Project C. Scrum Masters were selected through purposive sampling as respondents. Data were collected using a validated 66-item questionnaire with four response options: Yes, Partially, No, and Not Applicable. The achievement level of each Key Process Area was calculated using the Agile Maturity Model scoring formula. The findings show that Basic Scrum Management, Software Requirements Engineering, Iteration Management, and Performance Management were categorized as Fully Achieved. Customer Relationship Management was categorized as Largely Achieved, while Standardized Project Management was categorized as Partially Achieved. Overall, Software House XYZ's Scrum project management maturity was Level 3: Defined. This study contributes empirical evidence by conducting a project-level Scrum maturity assessment in a real software development organization, demonstrating how long-term Scrum adoption can still reveal inconsistencies in project standardization, Product Owner involvement, backlog management, and metric-based decision-making.